Ossifying haemangioma of the frontal sinus - Naim, Ramin; Steinhoff, Inga; Hörmann, Karl; Maurer, Joachim T. (ORL, 2004)
First described by Natali, the ossifying haemangioma is a rare entity. Although cases of ossifying haemangioma have been described in the literature, no involvement of the frontal sinus has been presented yet. We present a 46-year-old female patient who complained of recurrent cephalalgia and pressure in her forehead for 3 months. A computerized tomography scan demonstrated a compact radiopaque density arising from the floor of the middle cavity of her frontal sinus. Surgery was performed using the coronal approach. A rhomboid-shaped ossified tumour in the middle cavity of the frontal sinus was found with no signs of bleeding, partially obstructing the right sinus ostium. The small tumour was removed at the very base showing slight bleeding. Two weeks later, during the clinical follow-up, the patient did not complain of any of her previous symptoms. Previous studies have presented ossifying haemangioma of the temporal bone as an extremely aggressive entity affecting the 7th cranial nerve. In our case, the frontal sinus showed no signs of destruction of the adjacent tissue, and the only associated symptom was frontal cephalalgia. Because no critical surgical complications have been observed, no further changes to the surgical procedure appear necessary. We recommend performing a computerized tomography 6-12 months after surgery for follow-up to detect possible tumour regrowth.